The relevance of identity in languages education. Issue 2 (4th March 2022) - Evans, Michael; Fisher, Linda
ABSTRACT: Ofsted's 2021 Curriculum Research Review outlines a language pedagogy predicated on an exclusively cognitivist approach to language learning, which relies on three 'pillars of progression': phonics, vocabulary and grammar. The review makes a brief acknowledgement of the importance of motivational factors, including 'pupils' positive views of themselves as language learners' though these factors do not seem to inform its conclusions about what constitutes 'high-quality languages education'. Tellingly, the authors seem to believe that motivational factors are unrelated to learners' perceptions of the relevance of language learning in their lives. Addressing the issue of learners' perception of 'the relevance of languages in their lives' is indeed an important challenge, as the literature indicates, yet it is difficult to see how an exclusively cognitivist approach to language education can do this effectively. In this paper, we point to the growing recognition in languages education research of the key role played by multilingual identity development in successful language learning. We draw also on evidence from our recent AHRC-funded interventional study of Year 9 and Year 10 pupils (ages 13-15) in schools in England to argue for an identity-oriented language pedagogy as an integral component of a transformative approach to language learning.